Microbiological Study of Surfaces in the Hospital Environment Case of the Provincial Hospital of Sidi Kacem, Morocco - Elouakfaoui Aziz; Mahjoub aouane; Rouani Abdeljabbar; Berrid Nabyl (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: The hospital environment is largely colonized by pathogenic microorganisms. this contamination varies qualitatively and quantitatively according to the services and the capacity of the microorganisms to survive in inert environments, the elimination of these microorganisms requires a well formed staff and well detailed protocols which meet the international requirements. The microbiological monitoring of the hospital surfaces is a key factor to prevent nosocomial infections, it allows us to elaborate a diagnosis of the microbial ecology in order to lead preventive and corrective actions. Objective: The aim of our study is to identify the present bacteria on the surfaces of the provincial hospital of Sidi Kacem in Rabat-Salé-Kénitra region, Morocco, in order to reduce the rate of nosocomial infections.Methods: 167 samples were taken from different sites in the hospital wards, using the swabbing technique, according to ISO/DIS 14698-1, the identification of the isolated germs has been realized by the classical biochemical gallery and the API (Biomerieux, France).Results: A total of ten (10) bacterial species were isolated with a predominance of Bacillus sp (27%) and coagulase-negative staphylococci (29%), Staphylococcus aureus (18%), and Klebsiella pneumoniae (13%) followed. Thirteen (13) samples were a negative culture with a positivity rate of 92%. The distribution of isolated strains by department shows a predominance of bacterial strains in the intensive care unit (19%) and the emergency department (17%).Conclusion: These results show the importance of developing a risk management approach based on cleaning and disinfection protocols and procedures, as well as training and awareness programmers.